Type 3 Thyroplasty for a Patient with Female-to-Male Gender Identity Disorder - Yu Saito; Kazuhiro Nakamura; Shigeto Itani; Kiyoaki Tsukahara (Case Reports in Otolaryngology)
Objective. In most cases, about the voice of the patient with female-to-male/gender identity disorder (FTM/GID), hormone therapy makes the voice low-pitched. In success cases, there is no need for phonosurgery. However, hormone therapy is not effective in some cases. We perform type 3 thyroplasty in these cases. Method. Hormone therapy was started in 2008 but did not lower the speaking fundamental frequencies (SFFs). We therefore performed TP3 under local anesthesia. Results. In our case, the SFF at the first visit was 146 Hz. The postoperative SFF was 110 Hz. Conclusions. TP3 was performed under local anesthesia in a patient with FTM/GID in whom hormone therapy proved ineffective. With successful conversion to a lower-pitched voice, the patient could begin to live daily life as a male. QOL improved significantly with TP3. If hormone therapy proves ineffective, TP3 may be selected as an optional treatment and appears to show few surgical complications and was, in this case, a very effective treatment.